Unraveling Genomic and Pathogenic Features of Aeromonas ichthyocola sp. nov., Aeromonas mytilicola sp. nov., and Aeromonas mytilicola subsp. aquatica subsp. nov. - Nihed Ajmi; Muhammed Duman; Batuhan Coskun; Ceren Esen; Oner Sonmez; Gorkem Tasci; Orkide Coskuner-Weber; Hilal Ay; Digdem Yoyen-Ermis; Artun Yibar; Andrew P. Desbois; Izzet Burcin Saticioglu (Animals)
The Gram-negative genus Aeromonas contains diverse bacterial species that are prevalent in aquatic environments. This present study describes three novel Aeromonas strains: A. ichthyocola sp. nov. A-5T and A. mytilicola subsp. aquatica subsp. nov. A-8T isolated from rainbow trout (Oncorhynchus mykiss), and A. mytilicola sp. nov. A-7T isolated from mussels (Mytilus galloprovincialis), respectively. Genomic analyses revealed that strains A-5T and A-7T shared the highest 16S rRNA gene sequence similarity with A. rivipollensis P2G1T (99.7% and 99.8%, respectively), while strain A-8T exhibited 99.7% identity with A. media RMT. Together with morphological, physiological, and biochemical data, genome-based analyses provided additional evidence for species differentiation. Digital DNA–DNA hybridization (dDDH; 56.8−65.9%) and average nucleotide identity (ANI; 94.2–95.7%) values fell below the species delineation thresholds, confirming that these isolates represent distinct taxa. Pathogenicity assays using greater wax moth (Galleria mellonella) larvae demonstrated strain-specific virulence profiles. Further genomic analyses identified biosynthetic gene clusters for nonribosomal peptides (NRPs) and ribosomally synthesized and post-translationally modified peptides (RiPPs), which often have roles in secondary metabolite production. Ecological analyses, based on genomic comparisons and metagenomic database searches, revealed the adaptability of the strains to diverse habitats, including freshwater, wastewater, and activated sludge. Based on the genetic and phenotypic data, the novel taxa Aeromonas ichthyocola sp. nov. A-5ᵀ (LMG 33534ᵀ = DSM 117488ᵀ), Aeromonas mytilicola sp. nov. A-7ᵀ (LMG 33536ᵀ = DSM 117490ᵀ), and Aeromonas mytilicola subsp. aquatica subsp. nov. A-8ᵀ (LMG 33537ᵀ = DSM 117493ᵀ) are proposed.